Probable atomoxetine-associated acute hepatitis with hyperammonemia in a child with autism spectrum disorder and attention-deficit/hyperactivity disorder: A case report (Indian Journal of Case Reports, 2026)
Drug-induced liver injury is an important cause of acute hepatic dysfunction in children receiving neuropsychiatric medications. Atomoxetine, a selective norepinephrine reuptake inhibitor used in the treatment of attention-deficit/ hyperactivity disorder (ADHD), is generally well tolerated, although rare cases of hepatotoxicity have been reported. We describe a 5-year-old boy with autism spectrum disorder and ADHD who presented with fever, respiratory symptoms, and acute irritability. Laboratory evaluation revealed severe transaminitis with hyperammonemia, whereas bilirubin and coagulation parameters remained normal. The child had been started on atomoxetine, memantine, and piracetam 2 months before presentation. Withdrawal of the suspected medications and supportive therapy, including N-acetylcysteine, resulted in progressive clinical and biochemical improvement. This case highlights the importance of considering drug-induced liver injury in children presenting with sudden behavioral deterioration and abnormal liver function tests.